2017
DOI: 10.7759/cureus.1856
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Divisum: An Unusual Cause of Chronic Pancreatitis in a Young Patient

Abstract: Pancreatic divisum is a condition that occurs in 4-14% of the population. Pancreatic divisum occurs in development when the ventral bud and dorsal bud of the pancreas fail to fuse. Patients with this condition are usually asymptomatic, however, 25-38% of these patients experience recurrent pancreatitis that may further progress to chronic pancreatitis. This case is of a 20-year-old female presenting with abdominal pain in the left and right upper quadrants of the abdomen with a significant history of recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…19 Its incidence has been reported to be of approximately 4-14% of the population. 20 In the present radiological study, it was of 7.76%. The three subtypes of pancreas divisum were identified in the present MRCP study, which is similar to the findings of Adibelli et al 7 and Kamisawa and Okamoto.…”
supporting
confidence: 39%
“…19 Its incidence has been reported to be of approximately 4-14% of the population. 20 In the present radiological study, it was of 7.76%. The three subtypes of pancreas divisum were identified in the present MRCP study, which is similar to the findings of Adibelli et al 7 and Kamisawa and Okamoto.…”
supporting
confidence: 39%
“…MRCP is considered a non-invasive approach that can visualize the pancreatic ducts without the using of contrast-enhanced material. 12 MRCP is also a sensitive method for diagnosing PD. 13 An evidence-based review 14 showed that the sensitivity and specificity of MRCP for PD was 52% and 97%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic Divisum (PD) occurs in approximately 4-14% of the population [7]. PD has geographic variations, where it is found in approximately 4-10% of the Caucasian population and 1-2% of the Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…Type II pancreatic divisum is characterized by the absence of the ventral duct, so the minor papilla drains the entire pancreas and the major papilla drains some of the common bile duct. Finally, type III presents with a small remnant communication between the dorsal duct and ventral duct [7,8].…”
Section: Discussionmentioning
confidence: 99%